The outcome of filtration surgery in end-stage glaucoma - Gračner, Tomaž (Zdravniški vestnik, 2012)
Background: To evaluate the outcome of filtration surgery in end-stage glaucoma. Methods: This retrospective study included 20 eyes of 20 patients with different forms of endstage glaucoma in which goniotrephining with scleral flap without intraoperative antimetabolites was done. Intraocular pressure, best-corrected visual acuity, number of antiglaucoma medications and visual field test results before and after surgery were evaluated. Results: The follow-up after glaucoma surgery was 24 months in all eyes. The mean preoperative intraocular pressure was 26.9 mmHg (SD 6.7) and 12.6 mmHg (SD 3.2) at the end of follow-up; postoperatively it was lower at all follow-up visits (p < 0.0001). The mean preoperative best-corrected visual acuity was 0.44 (SD 0.3), 3 months postoperatively 0.42 (SD 0.3) (p = 0.253) and 0.28 (SD 0.2) at the end of follow-up (p = 0.023). The mean number of antiglaucoma medications was 3.0 (SD 0.4) preoperatively, decreasing postoperatively to a mean of 0.3 (SD 0.9) at the end of follow-up (p < 0.0001). Preoperatively, the mean value of the mean deviation in 11 eyes on automated perimetry was -27.49 dB (SD 2.1), and -27.73 dB (SD 1.6) postoperatively (p=0.289). Preoperatively, the mean visual field island in 9 eyes on Goldmann perimetry was 19.4° (SD 9.5), and 19.1° (SD 9.9) postoperatively (p=0.347). Conclusion: Filtration surgery in end-stage glaucoma followed for 24 months resulted in a significant and stable reduction of intraocular pressure and vision was preserved with no occurrences of "wipe-out" phenomenon.
Keywords: Filtering Surgery; Filtracijska kirurgija; Glaucoma; Glavkom; Intraocular Pressure; Izid zdravljenja; Kirurgija; Očesni pritisk; Surgery; Treatment Outcome; Vidna polja; Visual Fields